2021
DOI: 10.3390/molecules26113287
|View full text |Cite
|
Sign up to set email alerts
|

Antimutagenic, Cytoprotective and Antioxidant Properties of Ficus deltoidea Aqueous Extract In Vitro

Abstract: Ficus deltoidea var. deltoidea is used as traditional medicine for diabetes, inflammation, and nociception. However, the antimutagenic potential and cytoprotective effects of this plant remain unknown. In this study, the mutagenic and antimutagenic activities of F. deltoidea aqueous extract (FDD) on both Salmonella typhimurium TA 98 and TA 100 strains were assessed using Salmonella mutagenicity assay (Ames test). Then, the cytoprotective potential of FDD on menadione-induced oxidative stress was determined in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 32 publications
1
11
0
Order By: Relevance
“…These findings support the potential use of F. deltoidea for osteoporosis therapy in diabetes [28]. F. deltoidea aqueous extract at all concentrations tested (12.5-100 µg/mL) exhibited antioxidant power, suggesting the cytoprotective effect of F. deltoidea aqueous extract could be partly attributed to its antioxidant properties [27]. The report of T.C.…”
Section: Resultssupporting
confidence: 79%
See 3 more Smart Citations
“…These findings support the potential use of F. deltoidea for osteoporosis therapy in diabetes [28]. F. deltoidea aqueous extract at all concentrations tested (12.5-100 µg/mL) exhibited antioxidant power, suggesting the cytoprotective effect of F. deltoidea aqueous extract could be partly attributed to its antioxidant properties [27]. The report of T.C.…”
Section: Resultssupporting
confidence: 79%
“…Results showed that pretreatment of FDD (50 and 100 µg/mL) demonstrated remarkable protection against menadione-induced oxidative stress in V79 cells significantly by decreasing superoxide anion level. FDD at all concentrations tested (12.5-100 µg/mL) exhibited antioxidant power, suggesting the cytoprotective effect of FDD could be partly attributed to its antioxidant properties [27].…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…The level of reactive oxygen species (ROS), specifically for superoxide anion and hydrogen peroxide were assessed as previously described 63 , 64 . Briefly, the treated LN-18 cells were administered at different time-point intervals before being harvested.…”
Section: Methodsmentioning
confidence: 99%